What a Decade (2006–15) Of Journal Abstracts Can Tell Us about Trends in Ocean and Coastal Sustainability Challenges and Solutions - Rudd, Murray A. (Frontiers in Marine Science, 2017)
Text mining and analytics may offer possibilities to assess scientists’ professional writing and identify patterns of co-occurrence between words and phrases associated with different environmental challenges and their potential solutions. This approach has the potential to help to track emerging issues, semi-automate horizon scanning processes, and identify how different institutions or policy instruments are associated with different types of ocean and coastal sustainability challenges. Here I examine ecologically-oriented ocean and coastal science journal article abstracts published between 2006 and 2015. Informed by the Institutional Analysis and Development (IAD) framework, I constructed a dictionary containing phrases associated with 40 ocean challenges and 15 solution-oriented instrument or investments. From 50,817 potentially relevant abstracts, different patterns of co-occurring text associated with challenges and potential solutions were discernable. Topics receiving significantly increased attention in the literature in 2014-15 relative to the 2006-13 period included: marine plastics and debris; environmental conservation; social impacts; ocean acidification; general terrestrial influences; co-management strategies; ocean warming; licensing and access rights; oil spills; and economic impacts. Articles relating to global environmental change were consistently among the most cited; marine plastics and ecosystem trophic structure were also focal topics among the highly cited articles. This exploratory research suggests that scientists’ written outputs provide fertile ground for identifying and tracking important and emerging ocean sustainability issues and their possible solutions, as well as the organizations and scientists who work on them.